The like economy : how businesses are making money with Facebook - Carter, Brian, 1973- (Que, 2013)
The #1 Plan for Profiting from Facebook: Now Updated with New Tools, Techniques, Strategies! Brian Carter's complete, step-by-step Facebook sales and marketing plan has helped thousands of companies supercharge their online sales and profits. Now, he's completely updated it to reflect new Facebook features and tools, share all-new examples and experiences, and deliver actionable new insights about Facebook's users...your customers! Carter focuses on techniques proven to pay off and steers you away from expensive techniques that no longer work. You'll discover today's best ways to attract more prospects at lower cost, convert more of them into profitable buyers, repel "brand-bashers," and attract fans who'll help you sell. This is a book for doers, not talkers: entrepreneurs and marketers who want results, fast! • Compare Facebook's five routes to profit, and choose your best strategies • Craft a Facebook program that reflects your unique offerings and customers • Avoid eight key mistakes that kill Facebook profitability • Continuously optimize your presence to reflect your experience and performance • Sell the dream: Go beyond benefits to arouse your fans' desires • Attract super-affordable, targeted visitors and fans with Facebook ads • Deepen engagement by applying new insights about Facebook users • Improve branding, positioning, and customer service along with revenue • Master 13 proven influence tactics for transforming casual visitors into buyers • Employ time-tested sales tactics, including testimonials and upselling • Build a community you can translate into profits • Create a cost-effective B2B marketing program that works.